MODELO DE GESTION POR RESULTADOS PARA LA PLANIFICACION DE PROYECTOS SOCIALES DE LAS COMUNIDADES DEL GOBIERNO AUTONOMO DESCENTRALIZADO PROVINCIAL DE LOS RIOS - SANDRA PEPINA GIL MIRANDA (2013)
RESULTS-BASED MANAGEMENT MODEL FOR THE PLANNING OF SOCIAL PROJECTS OF THE COMMUNITIES OF THE PROVINCIAL DECENTRALIZED AUTONOMOUS GOVERNMENT OF LOS RIOS